2022
DOI: 10.1186/s12864-021-08282-x
|View full text |Cite
|
Sign up to set email alerts
|

Time-course RNASeq of Camponotus floridanus forager and nurse ant brains indicate links between plasticity in the biological clock and behavioral division of labor

Abstract: Background Circadian clocks allow organisms to anticipate daily fluctuations in their environment by driving rhythms in physiology and behavior. Inter-organismal differences in daily rhythms, called chronotypes, exist and can shift with age. In ants, age, caste-related behavior and chronotype appear to be linked. Brood-tending nurse ants are usually younger individuals and show “around-the-clock” activity. With age or in the absence of brood, nurses transition into foraging ants that show daily… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(62 citation statements)
references
References 209 publications
(184 reference statements)
3
59
0
Order By: Relevance
“…This resulted in Modules 4, 11 and 12 being indicated as day-peaking clusters and the other two (Modules 1 and 7) as night-peaking clusters (Figure 1A). Additionally, we found that the 'plasticity genes' that were significantly higher expressed in forager brains as compared to nurses 77 (for-UP) were significantly overrepresented in Module 9. In contrast, the genes that were significantly higher expressed in nurse brains (or, lower expressed in foragers, for-DOWN) were significantly enriched in Module 6.…”
Section: Link S B E T Ween Fung Al Manipul Ati On and Ant Pl A S Ti C...mentioning
confidence: 81%
See 4 more Smart Citations
“…This resulted in Modules 4, 11 and 12 being indicated as day-peaking clusters and the other two (Modules 1 and 7) as night-peaking clusters (Figure 1A). Additionally, we found that the 'plasticity genes' that were significantly higher expressed in forager brains as compared to nurses 77 (for-UP) were significantly overrepresented in Module 9. In contrast, the genes that were significantly higher expressed in nurse brains (or, lower expressed in foragers, for-DOWN) were significantly enriched in Module 6.…”
Section: Link S B E T Ween Fung Al Manipul Ati On and Ant Pl A S Ti C...mentioning
confidence: 81%
“…Indeed, a 24-h time-course study on C. floridanus foragers and nurses of the same colony demonstrated that foragers, entrained to provide 12-h:12-h LD cues, showed robust nocturnal foraging peaks, while nurses remained within the nest. 77 Conducting RNA-Seq on the brains of ants collected from these behavioural castes throughout a 24-h day showed that evident chronobiological differences in gene expression are plausibly underlying these phenotypes. Forager brains exhibited 24-h rhythmicity in three times more genes than nurse brains.…”
Section: Like Other Insects Ants Exhibit Daily Rhythms In Gene Expres...mentioning
confidence: 99%
See 3 more Smart Citations